Contribution of Vocational Pedagogy Courses on Students’ Readiness for Teaching Internship - Saif, Charisma Putrenesia; Gusnita, Wiwik; Elida, Elida; Sari, Yolanda Intan (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
This study aims to analyze the influence of the Pedagogical Vocational Course on students’ readiness to carry out the Educational Field Practice (PLK) among students of the Family Welfare Education Study Program, Universitas Negeri Padang, class of 2023. The background of this research is the low level of student readiness to face PLK, which is presumed to be related to the effectiveness of learning in the Pedagogical Vocational Course as an essential provision for preparing prospective professional teachers. This study employed a descriptive quantitative method with a correlational approach. The population consisted of 152 students, with a sample of 110 respondents determined using the Slovin formula. Data were collected using a four-point Likert scale questionnaire that had been tested for validity and reliability, and analyzed through simple linear regression and t-test. The results showed that students’ perceptions of the Pedagogical Vocational Course were in the medium to high category, while their readiness to carry out PLK was in the fairly good category. Based on the t-test, the significance value of 0.000 < 0.05 indicated a positive and significant influence of the Pedagogical Vocational Course on students’ readiness for PLK. The coefficient of determination (R²) value of 0.390 revealed that the Pedagogical Vocational Course contributed 39% to students’ readiness, while the remaining 61% was influenced by other factors outside this study.